2009
DOI: 10.1051/0004-6361/200811595
|View full text |Cite
|
Sign up to set email alerts
|

The solar chromosphere at high resolution with IBIS

Abstract: The structure and energy balance of the solar chromosphere remain poorly known. We used the imaging spectrometer IBIS at the Dunn Solar Telescope to obtain fast-cadence, multi-wavelength profile sampling of Hα and Ca II 854.2 nm over a sizable two-dimensional field of view encompassing quiet-Sun network. We provide a first inventory of how the quiet chromosphere appears in these two lines by comparing basic profile measurements in the form of image displays, temporal-average displays, time slices, and pixel-by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 44 publications
9
104
1
Order By: Relevance
“…Without micro-turbulence, the full width at half maximum (FWHM) of the chromospheric core, measured in our spatially resolved spectra is about 180 mÅ. Corresponding measurements from quiet-Sun line profiles were carried out by Cauzzi et al (2009), who found values in the range 450−550 mÅ. This means that our profiles are of the order of a factor 2.5 narrower than observed, assuming that instrumental degradation has a negligible effect on the FWHM of the profiles.…”
Section: Radiative Transfersupporting
confidence: 52%
“…Without micro-turbulence, the full width at half maximum (FWHM) of the chromospheric core, measured in our spatially resolved spectra is about 180 mÅ. Corresponding measurements from quiet-Sun line profiles were carried out by Cauzzi et al (2009), who found values in the range 450−550 mÅ. This means that our profiles are of the order of a factor 2.5 narrower than observed, assuming that instrumental degradation has a negligible effect on the FWHM of the profiles.…”
Section: Radiative Transfersupporting
confidence: 52%
“…As a result, we found that the velocity changes with wavelength in Ca II 8542 Å but this is not the case in Hα. This is because the Hα line is formed either in chromospheric fibrils or in the deep photosphere whereas the Ca II 8542 Å line samples the layer between them (Cauzzi et al , 2009. We speculate that the velocity changes with wavelength seen in Ca II 8542 Å may reflect an intrinsic property of the vertical flows above the pores/SMCs in the lower chromosphere.…”
Section: Vertical Motion In the Lower Chromospherementioning
confidence: 89%
“…Both lines showed fibrils with bright feet. Generally, darker Hα fibrils correspond to higher density, and Ca II brightness is more related to temperature (Cauzzi et al, 2009). Figure 3 shows the observation by Hinode/SOT for the ROI which is marked with a small box in Figure 1(a).…”
Section: Observation and Analysismentioning
confidence: 99%
See 2 more Smart Citations